The Development of Macrophomina phaseolina (Fungus) Resistant and Glufosinate (Herbicide) Tolerant Transgenic Jute - Majumder, Shuvobrata; Datta, Karabi; Sarkar, Chirabrata; Saha, Subhas C.; Datta, Swapan K. (Frontiers in Plant Science, 2018)
The worldwide demand for natural bast fibers is met aptly by the long, golden and silky fibers of jute. This highest bast fiber producing crop is of great applicability and is extensively used in paper and textile industry. Macrophomina phaseolina (Tassi) Goid is a severely devastating necrotrophic fungal pathogen causing stem rot, root rot, and charcoal rot diseases in both the cultivated species of jute – Corchorus capsularis and Corchorus olitorius. Another major problem faced in jute cultivation is profuse weed infestation in the fields. Huge losses in quality fiber production is caused by this pathogenic fungi and cultivation cost increases as well due to weed management expenditure during cropping season. To solve these long persisting jute cultivation challenges, the chitinase (chi11) gene (to provide fungus resistance) and the bar gene (to provide herbicide tolerance) have been incorporated in C. capsularis JRC-321 via Agrobacterium transformation and analyzed up to T2 generation. Stable integration and expression of these two genes in the jute genome was confirmed upon extensive analyses. Transgenic plants showed higher chitinase expression and chitin degrading activity than non-transgenic control plants. Antifungal activity significantly increased in transgenic plants as confirmed by detached leaf and whole plant M. phaseolina bioassay. Herbicide tolerance was analyzed by growing transgenic plants in 10 mg/l glufosinate ammonium containing media and by spraying 0.25% (v/v) glufosinate herbicide Basta® on them. Assessment of residual phytotoxicity effects of Basta® on soil confirmed no negative impact on growth of indicator plants corn and cucumber. Transgenic jute plants were at par with non-transgenic (control) jute plants in all phenotypic aspects. Non-transgenic (control) jute plants suffered significant losses in fiber yield and quality due to M. phaseolina infection whereas the transgenic lines maintained the quality of fiber even after the infection.